PENGAMATAN JENIS GULMA PADA TANAMAN POKOK JAGUNG (Zea mays L.)DI LAHAN SAWAH DESA BONGKASA ABIANSEMAL BADUNG, PROVINSI BALI - Krisna, Komang; Joni, Martin; Darmayasa, I. B.Gd. (SIMBIOSIS, 2019)
Research on weed inventory in maize land aims to see the diversity of existing weeds growing on the area of ??corn (Zea mays (L.)) in the fields of Bongkasa Abiansemal Badung Village, Bali Province. This observation will be expected to obtain information about the types of weeds that exist, so that weeds and control of weeds in corn (Zea mays (L.)) are optimally implemented. The study was conducted from June to August 2018. In observations using an exsplorating sampling method. In order to produce better and more systematic results, observations were made to make lanes and observations on the research land so that it could easily observe the growth of disturbing plants growing on the observed maize crops. In a 1-month old corn plant, 8 tribes were found with 16 species. In the 2month old corn plant, 14 tribes were found with 28 species of weeds, while in the 3-month-old maize there were 22 tribes with 40 species of weeds. The 22 tribes are Amaranthaceae, Asteraceae, Balsaminaceae, Capparidaceae, Commelinaceae, Convolvulaceae, Cyperaceae, Euphorbiaceae, Goodeniaceae, Laminaceae, Mimosaceae, Loganiaceae, Malvaceae, Onagraceae, Oxalidaceae, Poaceae, Portulacaceae, Rubiaceae, Scrophulariaceae, Solanaceae, Urtcaceae, Violaceae, Urtcaceae, with 40 species namely Amaranthus gracilis (Desf), Amaranthus spinosus (L), Ageratum conoyzoides L., Eclipta alba L., Emilia sonchifolia (L.), Vernonia cinerea (L, Synedrella nodiflora (L.), Tridax procumbens, Impatatiens platypetalaL Cleome rutidosperma DC, Cleome viscosaL, Murdania nudiflora (L.) Brenan, Impomea triloba L., Paedenia foetida L., Impomea gassicaulis Rot, Cyperus rotundus L. Kylliangia monocephala (Endl). Euphorbia hirta L. Phyllantus urinaria L., Phyllantus debilis Klein. Elephantopus scaber C., Basilicum polystachyon (L.), Mimosa pudica (L). Spigelia anthelmia L., Sida rhombifolia L., Ludwigia perennis L., Oxalis corniculata L. Dactyloctenium aegy ptium (L.), Digitaria ciliaris (Retz.), Eragrotis tenella (L.), Echinoclhoa colonum (L.), Elusine indica L., Portulaca oleraceae L., Hedyotis diffusa (L.) Lamk, Lindernia crustacea (L.), Scoparia dulcis L., Physalis angulata L., Capsicum frutescens, Urtica grandidentata L, Hybanthus attenuates L.   Keywords : weed, Zea mays L., Bongkasa Village .